The Protection of Seychelles’ Exclusive Economic Zone Through Penal Law: Analysing Warnakulusuriya Fernando v Republic [2000] and Kanapathi v R [2022] in the Light of Article 73(3) of United Nations Convention on the Law of the Sea - Mujuzi, Jamil Ddamulira (South African Yearbook of International Law, 2024)
Seychelles ratified the United Nations Convention on the Law of the Sea (UNCLOS) and Article 73(3) of this Treaty provides that ‘[c]oastal State penalties for violations of fisheries laws and regulations in the exclusive economic zone may not include imprisonment, in the absence of agreements to the contrary by the States concerned, or any other form of corporal punishment.’ Section 24 of the repealed 1986 Fisheries Act provided that a person convicted of fishing in Seychelles’ Exclusive Economic Zone (EEZ) without a licence was ‘liable to a fine.’ Although section 24 did not provide for imprisonment, in Warnakulusuriya Fernando v Republic [2000], the Supreme Court convicted the appellant and imposed a fine but also imposed a custodial sentence in default of payment of the fine. On appeal, he argued that the custodial sentence was contrary to Article 73(3) of UNCLOS. However, the Court of Appeal interpreted Article 73(3) as permitting imprisonment in such circumstances. In Kanapathi v R [2022] the Supreme Court convicted the appellant under section 11(1) of the 2014 Fisheries Act and imposed the mandatory fine and also ordered that in default of payment, the applicant was to undergo two years’ imprisonment. Because he could not afford to pay the fine, he had to serve a custodial sentence. He appealed against the sentence on the grounds that it was harsh. He also argued that the sentence was contrary to Article 73(3) of UNCLOS. All three judges agreed that the sentence was harsh and reduced it. However, one held that Article 73(3) of UNCLOS was applicable; another held that it was not applicable and the third one preferred not to express an opinion on the issue. None of the judges referred to Warnakulusuriya Fernando v Republic. Since this issue is very likely to re-emerge in the future, the author relies on, inter alia, the jurisprudence of the International Tribunal for the Law of the Sea to argue that Article 73(3) of the UNCLOS does not permit imprisonment, including imprisonment in default for paying a fine.